2022
DOI: 10.1186/s12874-021-01491-8
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging pleiotropic association using sparse group variable selection in genomics data

Abstract: Background Genome-wide association studies (GWAS) have identified genetic variants associated with multiple complex diseases. We can leverage this phenomenon, known as pleiotropy, to integrate multiple data sources in a joint analysis. Often integrating additional information such as gene pathway knowledge can improve statistical efficiency and biological interpretation. In this article, we propose statistical methods which incorporate both gene pathway and pleiotropy knowledge to increase stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…Pervasive genetic correlations between diseases allowed MTL to improve the PRS estimation broadly across diseases. While many cross-strait studies have shown the genetic correlation between specific pairs of diseases [18][19][20][21][22][23][24], our study suggested that various degrees of shared genetic basis may be very prevalent among many complex diseases. Our results highlighted the potential value of holistic association studies between the whole human phenome and the whole human genome for both risk variant discovery and PRS estimation.…”
Section: Plos Computational Biologycontrasting
confidence: 50%
See 1 more Smart Citation
“…Pervasive genetic correlations between diseases allowed MTL to improve the PRS estimation broadly across diseases. While many cross-strait studies have shown the genetic correlation between specific pairs of diseases [18][19][20][21][22][23][24], our study suggested that various degrees of shared genetic basis may be very prevalent among many complex diseases. Our results highlighted the potential value of holistic association studies between the whole human phenome and the whole human genome for both risk variant discovery and PRS estimation.…”
Section: Plos Computational Biologycontrasting
confidence: 50%
“…Many complex diseases share a substantial amount of common genetic determinants. Genome-wide cross-trait analyses have been performed between obesity and cardiovascular diseases [18], between thyroid and breast cancers [19], between uterine leiomyoma and breast cancer [20], between asthma and cardiovascular diseases [21], between Alzheimer's disease and gastrointestinal tract disorders [22], between Alzheimer disease and major depressive disorder [23], between lung cancer and chronic bronchitis [24], and so on. These studies were often motivated by frequent co-occurrences of pairs of diseases in a population.…”
Section: Introductionmentioning
confidence: 99%